Investigation of phytochemical and anti-bacterial activity On agave americana methanolic extract For medical applications - DR.V. KRISHNAVENI (International Journal of Pharma and Bio Sciences, 2017)
The outbreaks of human infections and diseases have been found in street vended contaminated fruit juices. So, there is a need to analyze the microbiological quality and safety of street vended juices for human consumption. The objective of this study was to analyze the microbiological quality of street vended sugarcane juice sold in Noida city, India. Total 40 samples of freshly extracted sugarcane juice from Noida city were collected and studied during the months of June 2013 to August 2013. The results indicated the pH of the collected samples in acidic range. MPN of samples (total coliforms) range from 9.4 MPN per 100 ml to >2400 MPN per 100 ml. Spread plate technique on standard agar showed the presence of Pseudomonas aeruginosa (25%), Salmonella spp (57.5%), Klebsiella spp (90%), S. aureus (82.5%) and Escherichia coli (72.5%) in the juice samples mainly due to unhygienic practices followed by the street vendors implying the immediate need of monitoring so as to improve microbial quality of juices.